Impact of the eHealth literacy, knowledge and attitudes on COVID-19 prevention behavior among residents in the second year of the COVID-19 pandemic: A cross-sectional study in Anhui Province, China - Yuan, Ting; Li, Xiang Dong; Zhang, Ming; Tao, Xiu Bin; Xu, Shu Juan; Liu, Huan (Frontiers in Public Health, 2022)
Objective ：The pandemic of COVID-19 continues to challenge people’s health worldwide. In the second year of the pandemic, adherence to COVID-19 preventive behaviours is key to continuing efforts to overcome the epidemic. This study aims to assess the COVID-19-related knowledge, attitude, and prevention behaviour (KAP) and electronic health literacy (eHealth) among Anhui residents in China. Method：From January 30 to March 27, 2021, the cross-sectional study was conducted among Anhui residents in China, including 16 cities. An online survey was adopted to assess KAP regarding COVID-19, and eHealth, involving a total of 2122 citizens. Following informed consent, residents were recruited by convenience sampling. Frequencies and proportions were calculated. Additionally, Mann-Whitney U tests were used to analyse the variables. Independent predictors of preventive behaviour of COVID-19 were ascertained using a multivariable logistic regression model. Result：Residents demonstrated good knowledge, positive attitudes, acceptable practices and good eHealth. Online news and WeChat are the main health information resources. Citizens who had good knowledge, positive attitude, good eHealth, did not participate in the online lectures or trainings on COVID-19were more likely to take preventive measures. Those who have a bad Health status, male, did not have family members worked in health care facilities, and did not work in face-to-face environment were less likely to take preventive measures. Compared with a master's degree and above, participants with middle school education level and below took preventive behaviours sometimes. Residents who browse the COVID-19 webpage less than <15 min everyday seldom took preventive actions. Conclusion： The study showed that in the second year of the COVID-19 pandemic, Chinese residents had adequate knowledge of COVID-19, positive attitudes, appropriate preventive practices, and basic eHealth literacy. To prevent the rebound of the COVID-19 epidemic, censoring the mainstream media, assisting the vulnerable population, and improving compliance with preventive behaviour are essential. In addition, increasing the level of knowledge and attitude, enhancing e-health literacy and the Health Belief Model (HBM), and implementing the Health Code was seen as a way to reinforce adherence to preventive behaviours. Men can be encouraged to comply with preventive behaviour by the reminders from women in the core family.